Vibration Analysis of Multilayered Human Anatomy in Seated Posture: Implications for Health and Comfort - Sachin Kalsi; Ishbir Singh; Sengundhar Dinesh Kovalan; Raman Kumar; T. Ramachandran; Aman Shankhyan; P. Vijaya Kumar; Vikasdeep Singh Mann; A. Bhowmik; A. Johnson Santhosh (Journal of Engineering)
The influence of machinery and transportation systems plays a crucial role in the development of human life. Humans encounter various kinds of vibration from the different environmental conditions such as air turbulence and bumpy roads; operating an excavator, machinery equipment, and so on causes a discomfort which affects the human health intensely. An attempt was made to reduce the impact of vibration on the human body by developing a 5-layered seated human anatomical structure that consists of the skeleton (bone), viscera (organs), nerves, muscles, and skin with the consideration of the Indian anthropometric dimensions belonging to the 95th percentile of the human male community and associated properties of the human tissue cells of different layers of the human body. The different modes of vibration that correlated with the natural frequencies of a human subject in a sitting posture were determined by performing the natural frequency analysis (modal analysis) using FEM approach. The resonant frequency of the multilayered human body was discovered in the range of 2–5 Hz with severe deformation observed in the hand, forelimb, and head due to low-frequency vibration that shall cause motion sickness and discomfort in the human subject. The frequency of resonance values of the present study was validated with the numerical study results available in the existing literature.